123k views
0 votes
The ratio (y+x) : (y-x) is equivalent to k : 1.Find an expression for y in terms of k and x.Y =?

User Whiz
by
7.5k points

1 Answer

4 votes

Final answer:

To find an expression for y in terms of k and x, we can set up the given ratio equation and solve for y to get y = -x(1 + k) / (1 - k).

Step-by-step explanation:

To find an expression for y in terms of k and x, we can set up the given ratio equation: (y + x) : (y - x) = k : 1.

Cross multiplying, we get (y + x) = k(y - x).

Distributing, we get y + x = ky - kx.

Combine like terms, we get y - ky = - x - kx.

Factor out y on the left side, we get y(1 - k) = -x(1 + k).

Finally, solving for y, we divide both sides by (1 - k) to get y = -x(1 + k) / (1 - k).

User Nkrivenko
by
7.8k points